Managerial Skills Improvement Of Finance And Management For Small Medium Enterprise - Armeliza, Diah; Nuramalia Hasanah; Indah Mulyasari (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
This community service activities are expected to provide skills for all SMES entrepreneurs to understand the business productivity, create simple financial records and reporting and conduct business management Proper financial management will be very helpful in fulfilling current and future life needs. By structuring a systematic business, entrepreneurs can view and analyze their capital turnover and take corrective steps of deviations from the original plan. Unfortunately, not all entrepreneurs have awareness about the importance of good business management. The community service activities are conducted in Matraman and Pulogadung sub-district to improve understanding and capability in business productivity, simple financial recording and reporting and business management . This community service is integrated into Student Study Service (KKN). The community service activities are conducted by providing training and mentoring/assistance to the entrepreneurs. Based on the results of the questionnaire can be concluded that participants satisfied with training and mentoring. This activity is expected to increase business productivity, financial management and business management.